Penerapan Metode Fuzzy Service Quality Untuk Menganalisa Kualitas Layanan Dan Produk Terhadap Kepuasan Pelanggan Pemasang Iklan Pada Koran Harian Kompas - Ngirfani, Muhammad; Purnia, Dini Silvi (The Indonesian Journal of Computer Science, 2022)
Kompas Daily Ads is a company engaged in the field of advertising services published in the Kompas Daily Newspaper. Advertising is a form of message to visit and provide information on goods or services. The current condition of the Covid-19 pandemic is a big challenge for Kompas Daily Ads to maintain the company's economy. One way that can be done is by paying attention to the quality of services and products to customers. Every customer certainly wants to get optimal service quality according to their expectations. Therefore, it is necessary to measure to determine the level of satisfaction felt by customers. Measurements were made using the Fuzzy Service Quality approach to determine perceptions and expectations based on five servqual dimensions, namely Tangible, Reliability, Responsiveness, Assurance, and Empathy. From the results of data processing, it is known that the attributes that need to be prioritized for improvement are the Reliability dimension on attribute 1: knowledge, and good development in serving customers with a gap value of -10.69. While the smallest gap value as an attribute with the best assessment by the seller is the Tangible dimension on attribute 4: The durability of advertisements printed on newspapers with a value of -2.22.